Diet and supplements and their impact on colorectal cancer - Pericleous, Marinos (Pioneer Bioscience Publishing Company, 2013)
BACKGROUND: Colorectal cancer is the third commonest cancer and the third leading cause of cancer death among men and women. It has been proposed that dietary factors are responsible for 70-90% of colorectal cancer and diet optimization may prevent most cases. AIM: To evaluate the role of dietary components and supplements in colorectal cancer. METHODS: Bibliographical searches were performed in Pubmed for the terms “diet and colorectal cancer”, “diet and colon cancer”, “diet and rectal cancer”, “nutrition and colorectal cancer”, “probiotics and colorectal cancer”, “prebiotics and colorectal cancer”, “alcohol and cancer” and “colorectal cancer epidemiology”. RESULTS: Consumption of processed or red meat, especially when cooked at high temperatures may be associated with increased risk of colorectal cancer. The evidence for dietary fibre is unclear but foods that contain high amounts of fibre are usually rich in polyphenols which have been shown to alter molecular processes that can encourage colorectal carcinogenesis. Meta-analyses provide evidence on the benefits of circulating, diet-derived and supplemented, vitamin D and Calcium. We also found that diets rich in Folate may prevent colorectal carcinoma. The evidence on dietary micronutrients such as Zinc and Selenium in association with colorectal cancer is not conclusive. It has been suggested that there may be a direct association between alcohol intake and colorectal cancer. In vitro and in vivo studies have highlighted a possible protective role of prebiotics and probiotics. CONCLUSIONS: The lack of randomized trials and the presence of confounding factors including smoking, physical activity, obesity and diabetes may often yield inconclusive results. Carefully designed randomized trials are recommended.